Validation of next-generation sequencing for comprehensive chromosome screening of embryos. Issue 6 (December 2015) - Kung, Allen; Munné, Santiago; Bankowski, Brandon; Coates, Alison; Wells, Dagan
Abstract: Massively parallel genome sequencing, also known as next-generation sequencing (NGS), is the latest approach for preimplantation genetic diagnosis. The purpose of this study was to determine whether NGS can accurately detect aneuploidy in human embryos. Low coverage genome sequencing was applied to trophectoderm biopsies of embryos at the blastocyst stage of development. Sensitivity and specificity of NGS was determined by comparison of results with a previously validated platform, array-comparative genomic hybridization (aCGH). In total, 156 samples (116 were blindly assessed) were tested: 40 samples were re-biopsies of blastocysts where the original biopsy specimen was previously tested for aCGH; four samples were re-biopsies of single blastomeres from embryos previously biopsied at the cleavage stage and tested using aCGH; 18 samples were single cells derived from well-characterized cell lines; 94 samples were whole-genome amplification products from embryo biopsies taken from previous preimplantation genetic screening cycles analysed using aCGH. Per embryo, NGS sensitivity was 100% (no false negatives), and 100% specificity (no false positives). Per chromosome, NGS concordance was 99.20%. With more improvement, NGS will allow the simultaneous diagnosis of single gene disorders and aneuploidy, and may have the potential to provide more detailed insight into other aspects of embryo viability.